Antagonistic SnRK2 and PID kinases' action on auxin transport–mediated root gravitropism - Fang Sheng; Yu Gao; Yaping Wang; Yang Li; Ji-Ao Zhang; Zhaoheng Zhang; Xinyan Qin; Shujuan Zhang; Wen Song; Jigang Li; Yan Guo; Jiří Friml; et al. (Proceedings of the National Academy of Sciences, 2025)
Plants have evolved sophisticated mechanisms to adapt to environmental changes, with root gravitropism playing a pivotal role in nutrient and water acquisition. Our study reveals that SnRK2 kinases (SnRK2.2 and SnRK2.3) are critical regulators of root gravitropism through their direct phosphorylation of the auxin transporter PIN2 at S259. We demonstrate that SnRK2s-mediated phosphorylation modulates both the polar localization and transport activity of PIN2. Importantly, SnRK2s function antagonistically to the AGCVIII kinase PID, which phosphorylates PIN2 at a distinct site (S258), establishing a regulatory balance essential for adaptive root growth. Structural modeling and phosphorylation assays further suggest that SnRK2s-mediated phosphorylation at S259 sterically hinders access of PID to S258, providing a mechanistic basis for their antagonistic relationship. These findings uncover a novel regulatory mechanism, by which plants fine-tune root developmental programs to adapt to environmental stimuli, highlighting the evolutionary significance of multilayered kinase-mediated regulation in plant adaptation.